Linking Gender, Environment, and Poverty for Sustainable Development : A Synthesis Report on Ethiopia and Ghana - World Bank (Washington, DC, 2012)
Poverty, environment, social development, and gender are important cross-cutting themes of the World Bank and government investment programs, especially within the Sustainable Development Network (SDN). For developing sectoral strategies and programs, economic, environment and social assessments are undertaken, however, these are usually done separately, and most often gender issues are not included. This is a missed opportunity, because joint assessments can map the links between gender, environment, and poverty and help identify approaches that can accelerate the positive synergy and better social/gender, environment, and poverty outcomes; otherwise, the existing negative relationships may slow the development process, and can even lead to unintended results. A joint analysis will also reduce cost of project preparation. This study was undertaken to analyze the links between gender, environment, and poverty; identify approaches; and provide practical suggestions for fostering positive synergies for better outcomes. The analytical framework for this study draws on the World Bank's three pillars of sustainable development: social inclusion, economic growth and environmental sustainability, and from political ecology literature, which highlights how decision-making processes, power relationships, and social conditions influence environmental policies and development outcomes. The following four propositions derived from political ecology literature guide the analysis: i) socioeconomic marginalization and natural resource degradation are mutually reinforcing processes; ii) protected area conservation and external control of natural resources can disrupt household and community production and social organization; iii) competing environmental interests shape environmental change; and iv) collective action and resilience can help mitigate negative impacts. The study is based on in-depth analysis of two sub-Saharan African countries Ethiopia and Ghana. The research methodology was qualitative, and included a series of interrelated analyses: a political ecology literature review, country-specific reviews of literature and data sets, good-practice project case studies in both countries, and participatory appraisals of grassroots perceptions of gender-poverty-environment links. Study sites were selected to include the major agro ecological zones and rural livelihood systems in each country. National and sub regional participatory forums were conducted to 'ground truth' the findings and elicit policy and project recommendations. A seven-week online discussion explored the broader applicability of the framework and study findings.